Upper limb stretch reflex dynamics in male judo athletes - Ito, S.; Nakagawa, K.; Kato, K.; Kanosue, K.; Iteya, M. (Journal of Sports Sciences, 2025)
In this study, we aimed to assess the upper limb stretch reflex characteristics in judo athletes. Overall, 15 experienced judo athletes (mean experience: 13.4 ± 3.1 years) and 15 controls were evaluated using two perturbation types, abrupt passive elbow extension (flexor stretching) and flexion (extensor stretching) induced by a dynamometer. During extension perturbations, participants relaxed or flexed their elbows upon detection, while during flexion perturbations, they relaxed or extended their elbows. Stretch reflexes were recorded via right biceps and triceps brachii surface electromyography (EMG). Reflex components were categorised as M1 (20-50 ms), M2 (50-80 ms), and M3 (80-100 ms). Judo athletes had a significantly higher triceps brachii M3 component than that of the control group during elbow extension on flexion perturbation with no differences in M1 and M2, irrespective of the task type. Similarly, judo athletes had a significantly higher biceps brachii M3 component than that of the control group during elbow flexion on extension perturbation with no differences in M1 or M2. No differences were observed in any components between the groups during relaxation on perturbation. Our study suggests that experienced judo athletes enhanced their long-latency stretch reflex in the triceps and biceps brachii muscles.